Organ Transplantation in the Perspective of Islamic Fiqh: Analysis of Permissibility, Requirements, and Legal Implications - Chaisya Aliffah Siswoyo; Yulia; Eviana Sagala; Ahmad Baqi (Jurnal Sahabat ISNU SU, 2024)
Organ transplantation represents one of the most significant advances in modern medicine, offering life-saving treatment and improving the quality of life for patients suffering from end-stage organ failure. Nevertheless, this medical practice raises important legal and ethical questions within Islamic jurisprudence (fiqh), particularly concerning the permissibility of organ donation, the protection of human dignity, and the prohibition of organ commercialization. This study aims to analyze the Islamic legal perspective on organ transplantation, examine the conditions governing organ donation from living and deceased donors, and explore the legal implications of organ trading within contemporary medical practice. This research employs a qualitative normative approach through library research by analyzing primary Islamic legal sources, including the Qur'an, Hadith, classical and contemporary fiqh literature, fatwas, and relevant scholarly publications. The findings reveal that the majority of contemporary Muslim scholars permit organ transplantation under strict conditions, namely medical necessity (ḍarūrah), voluntary donor consent, the absence of serious harm to the donor, and the prohibition of any commercial motive. Organ donation from deceased individuals is also considered permissible, provided prior consent or family authorization exists and the dignity of the deceased is respected. Conversely, the commercialization and sale of human organs are categorically prohibited because they violate the principles of human dignity (karāmat al-insān), justice, and the objectives of Islamic law (maqāṣid al-sharī‘ah). The study concludes that organ transplantation is compatible with Islamic law when conducted within ethical and legal boundaries aimed at preserving human life (ḥifẓ al-nafs). Therefore, stronger legal regulation, public education, and collaboration between medical professionals and Islamic scholars are essential to ensure that transplantation practices remain consistent with Islamic ethical principles.